Ascorbic acid efflux from human brain microvascular pericytes: Role of re‐uptake. (4th September 2015) - May, James M.; Qu, Zhi‐Chao
Abstract Microvascular pericytes take up ascorbic acid on the ascorbate transporter SVCT2. Intracellular ascorbate then protects the cells against apoptosis induced by culture at diabetic glucose concentrations. To investigate whether pericytes might also provide ascorbate to the underlying endothelial cells, we studied ascorbate efflux from human pericytes. When loaded with ascorbate to intracellular concentrations of 0.8–1.0 mM, almost two‐thirds of intracellular ascorbate effluxed from the cells over 2 H. This efflux was opposed by ascorbate re‐uptake from the medium, since preventing re‐uptake by destroying extracellular ascorbate with ascorbate oxidase increased ascorbate loss even further. Ascorbate re‐uptake occurred on the SVCT2, since its blockade by replacing medium sodium with choline, by the SVCT2 inhibitor sulfinpyrazone, or by extracellular ascorbate accelerated ascorbate loss from the cells. This was supported by finding that net efflux of radiolabeled ascorbate was increased by unlabeled extracellular ascorbate with a half‐maximal effect in the range of the high affinity Km of the SVCT2. Intracellular ascorbate did not inhibit its efflux. To assess the mechanism of ascorbate efflux, known inhibitors of volume‐regulated anion channels (VRACs) were tested. These potently inhibited ascorbate transport into cells on the SVCT2, but not its efflux. An exception was the anion transport inhibitor DIDS, which, despite inhibition of ascorbate uptake, also inhibited net efflux at 25–50 µM. These results suggest that ascorbate efflux from vascular pericytes occurs on a DIDS‐inhibitable transporter or channel different from VRACs. Further, ascorbate efflux is opposed by re‐uptake of ascorbate on the SVCT2, providing a potential regulatory mechanism. © 2015 BioFactors, 41(5):330–338, 2015